Studi Struktur Lapisan Tanah pada Dusun Tamalalang Timur, Kabupaten Gowa sebagai Pendeteksi Awal Daerah Rawan Longsor - Sulistiawaty Sulistiawaty; Pariabti Palloan; Ridwansyah Ridwansyah; Vistarani Arini Tiwow; Muh. Ais Andika (JKM: Jurnal Kemitraan Masyarakat, 2026)
Landslides are a type of natural disaster that often occurs in areas with hilly and mountainous topography with high rainfall. Tamalalang Timur Hamlet, Gowa Regency, South Sulawesi is a geomorphologically located area in a hilly area with high rainfall, so it has a significant potential for landslides. This community service activity aims to analyze the structure of the soil layers in Tamalalang Timur Hamlet using the Wenner-Schlumberger configuration geoelectric resistivity method and provide socialization to the community about the categories of landslide-prone areas. Measurements were carried out in areas that represent the topographic and geological conditions that are the target of the service. The results of resistivity data inversion indicate that the soil layers in the area are dominated by water-saturated clay with a low resistivity value of 1–12 Ωm, followed by sandy clay soil layers (12.7–50 Ωm) and bedrock (>100 Ωm). From the interpretation, it provides a strong indication of the existence of a tiered rock layer system, with the potential for aquifers located in the middle layer with moderate to low resistivity, while the base layer is made of hard, impermeable rock. On the one hand, the public needs easy-to-understand information about the early signs of landslides. Some people are more familiar with the dangers of flooding than local landslides or land subsidence. Therefore, this activity provides practical benefits in the form of increased disaster literacy.